Increasing access to Higher Education: A study of the diffusion of online teaching among 913 college faculty - Shea, Peter; Pickett, Alexandra; Li, Chun Sau (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
Online learning environments provide an unprecedented opportunity to increase student access to higher education. Accomplishing this much needed goal requires the active participation and cooperation of university faculty from a broad spectrum of institutional settings. Although online learning has seen rapid growth in recent years, it remains a relatively small percentage of the entire curriculum of higher education today. As a relatively recent development, online teaching can be viewed through the lens of diffusion of innovation research. This paper reports on research from 913 professors from community colleges, four-year colleges, and university centers in an attempt to determine potential barriers to the continued growth in adoption of online teaching in higher education. It is concluded through factor and regression analysis that four variables are significantly associated with faculty satisfaction and their likelihood, therefore, to adopt or continue online teaching – these include levels of interaction in their online course, technical support, a positive learning experience in developing and teaching the course, and the discipline area in which they taught. Recommendations for institutional policy, faculty development, and further research are included.